Incubation period of Clostridioides difficile infection in hospitalized patients and long-term care facility residents: a prospective cohort study - Scott R. Curry; Michelle T. Hecker; Justin O'Hagan; Preeta K. Kutty; Yilen K. Ng-Wong; Jennifer L. Cadnum; Heba Alhmidi; Melany I. Gonzalez-Orta; Carlos Saldana; Brigid M. Wilson; Curtis J. Donskey (Cambridge University Press, 2024)
Abstract Background: The incubation period for Clostridioides difficile infection (CDI) is generally considered to be less than 1 week, but some recent studies suggest that prolonged carriage prior to disease onset may be common. Objective: To estimate the incubation period for patients developing CDI after initial negative cultures. Methods: In 3 tertiary care medical centers, we conducted a cohort study to identify hospitalized patients and long-term care facility residents with negative initial cultures for C. difficile followed by a diagnosis of CDI with or without prior detection of carriage. Cases were classified as healthcare facility-onset, community-onset, healthcare facility-associated, or community-associated and were further classified as probable, possible, or unlikely CDI. A parametric accelerated failure time model was used to estimate the distribution of the incubation period. Results: Of 4,179 patients with negative enrollment cultures and no prior CDI diagnosis within 56 days, 107 (2.6%) were diagnosed as having CDI, including 19 (17.8%) with and 88 (82.2%) without prior detection of carriage. When the data were censored to only include participants with negative cultures collected within 14 days, the estimated median incubation period was 6 days with 25% and 75% of estimated incubation periods occurring within 3 and 12 days, respectively. The observed estimated incubation period did not differ significantly for patients classified as probable, possible, or unlikely CDI. Conclusion: Our findings are consistent with the previous studies that suggested the incubation period for CDI is typically less than 1 week and is less than 2 weeks in most cases.